Seven new species of Amphidraus Simon, 1900 (Araneae: Salticidae: Euophryini) - Salgado, Alexandre; Ruiz, Gustavo R.s. (Zootaxa, 2019)
Seven new species of Amphidraus Simon, 1900 are described from Brazil: A. araripe sp. nov. (♂♀), A. boomerang sp. nov. (♂), A. cornipalpis sp. nov. (♂♀), A. draconitupan sp. nov. (♂♀), A. manauara sp. nov. (♂♀), A. sacrificatus sp. nov. (♂) and A. shenlong sp. nov. (♂). Morphological variation in the male palp of A. draconicaudatus Salgado & Ruiz, 2017 and A. caxiuanan Salgado & Ruiz, 2017 is discovered and evaluated.